AKAP350 Interaction with cdc42 Interacting Protein 4 at the Golgi Apparatus - Larocca, M. Cecilia (The American Society for Cell Biology, 2004)
The A kinase anchoring protein 350 (AKAP350) is a multiply spliced type II protein kinase A anchoring protein that localizes to the centrosomes in most cells and to the Golgi apparatus in epithelial cells. In the present study, we sought to identify AKAP350 interacting proteins that could yield insights into AKAP350 function at the Golgi apparatus. Using yeast two-hybrid and pull-down assays, we found that AKAP350 interacts with a family of structurally related proteins, including FBP17, FBP17b, and cdc42 interacting protein 4 (CIP4). CIP4 interacts with the GTP-bound form of cdc42, with the Wiscott Aldrich Syndrome group of proteins, and with microtubules, and exerts regulatory effects on cytoskeleton and membrane trafficking. CIP4 is phosphorylated by protein kinase A in vitro, and elevation of intracellular cyclic AMP with forskolin stimulates in situ phosphorylation of CIP4. Our results indicate that CIP4 interacts with AKAP350 at the Golgi apparatus and that either disruption of this interaction by expressing the CIP4 binding domain in AKAP350, or reduction of AKAP350 expression by RNA interference leads to changes in Golgi structure. The results suggest that AKAP350 and CIP4 influence the maintenance of normal Golgi apparatus structure.